Depression Level Can Affect The Quality of Life in Tuberculosis Patients - Ramadina, Rizma Dwi; Wahyuni, Lutfi; Nur So’emah, Eka (Jurnal Psikiatri Surabaya, 2026)
Introduction: Patients with tuberculosis often struggle not only with the burden of physical illness but also significant psychological challenges, especially depression, that affect their quality of life profoundly. Method: The research strategy was correlation analytic with a cross-sectional approach. The sample size was 100 respondents. Purposive sampling was utilized in this study. The researchers used the World Organization on Quality of Life Bref (WHOQOL-BREF) and the Depression Anxiety Stress Scales (DASS-21) as tools. Results: The results obtained were that most of the respondents had a normal level of depression, as many as 70 respondents (70%), while 94 respondents (94%) had a satisfactory standard of life. The data analysis used Spearman Rho, which obtained a significance value of ρ-value = 0.000 with a correlation coefficient value of r = 0.485, indicating a moderate and positive relationship between depression and quality of life in tuberculosis patients. Tuberculosis patients’ quality of life improves when their depression level decreases. Conclusions: The study’s conclusion is the relationship between depression and quality of life in tuberculosis patients at the public health center Sooko Mojokerto.